Pengaruh Pendidikan Kesehatan terhadap Tingkat Pengetahuan Mahasiswi Tingkat I Program Studi S1 Keperawatan tentang Pemberian Kompres Hangat dalam Penanganan Nyeri Haid (Dismenore) di Stikes Eka Harap Palangka Raya - Vita Natalia; Neneng Safitri; Rizki Muji Lestari; Devi Novia (Jurnal Surya Medika (JSM), 2022)
Background: Pain during the menstrual period is called dysmenorrhea. This pain is felt in the lower side of the abdomen or Michaelis. The pain can be felt before, during, or after menstruation and can be colic or continuous. Students said that they experienced pain during menstruation. A warm compress can relieve the pain because its function is to improve blood circulation. Objective: The effect of health education on knowledge levels of first years students of the nursing study program about giving warm compress to deal with dysmenorrhea in STIKes Eka Harap Palangka Raya. Methods: This research used a pre-experimental method with one group pretest-posttest design. The sample was chosen using total sampling, which consisted of 52 respondents with students with IA and IB degrees. The data were collected using a questionnaire and analyzed using non-parametric statistics Wilcoxon signed ranks test. Results: Based on the statistical test of Wilcoxon signed ranks test with p-value was 0.05, because the sig asymp value=0.000, then ho was rejected which means that there is an effect of health education on knowledge levels. Conclusion: It was concluded that there is an increased level of knowledge after being given health education. Expected further research can develop research on various menstrual disorders in female students.